Explaining adoption of management innovations in less advanced settings: evidence from Turkey - Erçek, Mehmet (Journal of Business Economics and Management, 2014)
This study aims to explain how globally circulating management innovations are adopted by the firms operating in less advanced settings based on an integrative framework. The framework incorporates certain characteristics of national business systems, particular inter-organizational ties developed with transnational or local carriers, and the potential absorptive capacity of the local organizations. By this way, it includes the effects of temporal interactions between different adoption decisions. The components of the framework are operationalized and tested within the Turkish setting by using the adoption data of three different management innovations: TQM, six sigma and lean production. The data is collected from a sample of 375 large-sized firms using a telephone-based interview protocol. While the findings provide satisfactory support for the framework as a whole, they also call attention to the relative differences in the explanatory power of each factor in accounting for the adoption of particular innovations. Variations among the explanatory factors can be attributed to the differences between the life-cycles of TQM, six sigma and lean production as well as to the relative divergence of their conceptual framing.